Food properties influence grasping strategies in strepsirrhines. (15th February 2019) - Peckre, Louise R; Fabre, Anne-Claire; Hambuckers, Julien; Wall, Christine E; Socias-Martínez, lluís; Pouydebat, Emmanuelle
Abstract: Although hand grasping is ubiquitous in primate species, its origins remain uncertain. This is in part because uncertainty about hand skills and grasping strategies persists in strepsirrhines, a monophyletic group of primates located near the base of the primate tree. In this study, we report and discuss our observations of the different grasping strategies adopted by 85 captive individuals belonging to 22 species of strepsirrhines during the grasping of food items of different sizes and consistencies. Our results indicate that although strepsirrhines do not present variability in their hand-grip types (sole whole-hand power grip), they are able to adjust their grasping strategy depending on the properties of the food. Notably, they use the mouth when more precision is needed (i.e. to grasp small items). Moreover, grasping strategies adopted for big items differ depending on food consistency, revealing a new and potentially essential factor to consider in future research on grasping abilities. We believe that by looking across this important set of species in unconstrained standardized conditions, this study provides valuable insight for further comparative research on the potential selective pressures involved in the evolution of hand grasping.